Hubungan Motivasi Belajar dengan Prokrastinasi Akademik Siswa - Nitami, Mayrika; Daharnis, Daharnis; Yusri, Yusri (Konselor, 2015)
Academic procrastination is a bad behavior because it obstructs the students to achieve the goal of learning. Procrastination is affected by some factors, one of them is learning motivation. Students attract to do their homework, although they do it at school, late report and disturb their friend in learning. All of that are characteristics of academic procrastination. The research purposes are to describe student learning motivation, academic procrastination, and the correlation of learning motivation and academic procrastination of student at SMP N 25 Padang. This research is a descriptive correlational. The population are 482 students of class VII and class VIII SMP N 25 Padang. The samples are 233 students who gained by proportional random sampling. The instrument is learning motivation questionnare and academic procrastination questionnare. The data is analyzed by descriptive statistic method and pearson product moment correlation.The results show that 1) student’s learning motivation is categorized high, 2) student’s academic procrastination is categorized medium, 3) there is negative correlation between learning motivation with academic procrastination of students. The coefficient correlation is r -0,636 with significant 0,000. The higher motivation that the students have the lower their academic procrastination. Therefore students learning motivation can prevent academic procrastination. Guidance and counseling teachers have to help increase their learning motivation and solve their academic procrastination by guidance and counseling services.